Optimal Homotopy Asymptotic Method for Solving the Linear Fredholm Integral Equations of the First Kind - Mohammad Almousa; Ahmad Ismail (Abstract and Applied Analysis)
The aim of this study is to present the use of a semi analytical method called the optimal homotopy asymptotic method (OHAM) for solving the linear Fredholm integral equations of the first kind. Three examples are discussed to show the ability of the method to solve the linear Fredholm integral equations of the first kind. The results indicated that the method is very effective and simple.